The design thinking as methodology in the contemporary legal education (Research, Society and Development, 2020)
The contemporary legal educational process lives a deep changing moment. This is a result of the professional market’s demands. The professional market impacted by the technological revolution and the globalization claims for more qualified and professionals in terms of skills and projects’ development. The legal education has been changing deeply in order to follow the market’s exigences. In this regard, this current paper aims to o report a practical experience of using design thinking methodology, also the qualitative scientific method and the descritive case study. It was intendeded to show and it concluded that the tool has applicability and can serve as a pedagogical methodology in law courses.